Gerenciamento de resíduos em unidades de saúde de Santa Maria/RS: avaliação de uma ação da vigilância sanitária municipal - Delevati, Dionatan dos Santos (2020)
Due to the risk to public health and the environment, it is important to the management of Health Service Waste (HSW), especially by health professionals, who sometimes do not comply with the legislation or the difficulty of access to information, are difficult to make decisions about the management of HSW. The present study aims to evaluate whether a health intervention carried out by the Health Surveillance (HS) of the city of Santa Maria/RS contributed to the improvement of the management of Health Service Waste (HSW) generated in the Health Units (HU) of the municipality. This is a near-experimental study in which two health inspections were carried out in health units, one before and after the health intervention performed by the local VISA. The health intervention consisted of the training of one or two higher level professionals from each unit for Health Services Waste Management (HSWM) with a performance test, as well as the subsequent availability for technical consulting in the area of GRSS via the Internet or scheduled visit during the three-month period, and a semi-structured interview was conducted with a professional from each unit after this period. The study included 25 health units in the municipality, which, among the participants of the training, 74% were used in terms of acquired knowledge, however, 76% did not pass on the information acquired to their health team. In an interview, a total of 52% of the participants feel qualified to prepare the Health Waste Management Plan (HWMP) of their unit, however, 38% are from units that stated that they do not own and do not know the PGRSS. The data presented indicate that, despite the reduction in non-conformities verified during the return inspection regarding the packaging of 44% of the units and in the identification of waste collectors in 32% units, regardless of the intervention of the study, these did not result in the reduction of non-conformities in segregation, which presented an increase in non-conformities after the intervention. After the intervention, the reduction of non-conformities in packaging, management of sharp-cutting waste and internal storage was identified. However, these practices were not associated with the health intervention that was submitted (p>0.05). Therefore, the intervention had no overall effect on the PGRSS. This may be a consequence of the lack of theoretical and practical knowledge at this stage of the process or the absence of Permanent Health Education (PHE) practices focused on the theme investigated, or the inefficiency of specific health education activities. In this sense, it is necessary to strengthen the PHE process in primary care, contributing to the consolidation of environmental values, promoting quality of life associated with preservation and sustainability.